Factors in the Neonatal Period Associated With Pulmonary Hypertension at 28 Days of Life in Broncho-Pulmonary Dysplasia - Nguyen Thi Hai Anh MD; Tran Minh Dien PhD; Le Thi Ha MD; Pham Thao Nguyen MD; Dang Thi Hai Van PhD (SAGE Publishing, 2024)
Objectives. To identify factors associated with pulmonary hypertension (PH) at 28 days of life in preterm infants with bronchopulmonary dysplasia (BPD). Methods . This observational study included 128 premature infants with BPD between January 2022 and February 2023 from the neonatal intensive care unit of Vietnam National Children's Hospital. Results . PH was observed using echocardiography in 29 patients (22.66%). The prevalence of severe BPD in the PH group (62.07%) was significantly higher than that in the non-PH group (18.18%). The multivariate logistic regression showed 2 predictors of PH in BPD: invasive mechanical ventilation up to 28 days of life (odds ratio [OR]:9.440; 95% confidence interval [CI]: 3.090-28.833; P  < .001) and history of shock (OR: 2.962; 95% CI: 1.067-8.225; P  = .037). Conclusion. We found 2 predictors of PH at 28 days of life in BPD: invasive mechanical ventilation up to 28 days of life and history of shock.